Brief chewing of Garcinia manii stick reverses reduced saliva pH after a glucose rinse - Addai, F.K.; Nuamah, I.K.; Parkins, G.E. (Medical Science Monitor, 2002)
BACKGROUND: A popular variety of wood, pieces of which are chewed as an oral hygiene practice in Southern Ghana, was tested for its capacity to reverse experimentally lowered pH of saliva. This was done to determine whether (Garcinia manii) stick-chewing neutralizes acidogenic challenge to teeth, and thereby potentially affords dental caries prevention benefit. MATERIAL/METHODS: Seventy-two volunteer medical students gave (baseline) saliva samples by spitting 3-4 times into a 25 ml conical flask. They then rinsed their mouths with a five-percent aqueous solution of glucose. Subsequent to the glucose rinse, half of the subjects (chewers), pre-selected by drawing lots, chewed a popular chewing stick Garcinia manii for five minutes, while the other half (controls) did not. The pH of saliva samples given by the volunteers at various time intervals was measured using a Kent EIL 7020 pH meter, and the results were analysed by the Analysis of Variance (Anova) method. RESULTS: As expected, saliva pH was reduced in both groups after the glucose rinse, but increased significantly faster in stick chewers compared with controls. CONCLUSIONS: It is suggested from this study that brief (Garcina manii) stick-chewing confers a caries prevention/control benefit by reversing acidogenic challenge to teeth.